Security and confidentiality of information and its impact on the competitive performance of insurance companies: A prospective study for the Iraq insurance company and ALhamraa Insurance company (private) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The security of information represent the available  protection of  information and its component and guaranty the its safety and confidentiality. The absent or lack or stop of security of information and without maximum benefit may lead to lose confidence and make it burden on the company. So we must protect the company and information from the damages which may lead to the frailer of performance and loses of the company and its workers. So the security of information considered one of the potential  and controlling basis to protect individuals and companies from the damages. To insure the security  and confidentiality of information there are delicate,  proper and trusted ways, like FIRE WALL, PASS WORD, SYPHAR, and so on, in order to prevent leakage of stored data and information which may affect the competitive performance of the insurance companies and leading to lose and not available in the market of insurance.On these bases the researcher took into consideration in her research (Security and Confidentiality of information and its impact on the competitive performance of insurance companies).This research is applied in the Iraqi General Company of Insurance and ALhamraa private company of insurance as a sample of insurance companies in Iraq and tests a sample from directors and staff (70 persons) in the two companies. A special information form has used to collect information, data are used to test the hypotheses of research, to test  hypotheses a lot of statistical methods have used and concluded a certain results. The research has reached a number of conclusions, the most important one is the connection and affect between the security and confidentiality of information  and the mentioned competitive performance of the insurance companies. The results matched hypotheses of the research. The researcher has concluded a set of recommendations to the mentioned company, one of important results is that the two companies should take actions and procedures to circulate the culture of the security and confidentiality of in formations on different administrative level through training courses.